2003
DOI: 10.1016/s1476-5586(03)80040-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Optical Tomographic Imaging of Malignant and Benign Breast Lesions: Initial Clinical Results of 19 Cases

Abstract: The diagnosis of solid benign and malignant tumors presents a unique challenge to all noninvasive imaging modalities. Ultrasound is used in conjunction with mammography to differentiate simple cysts from solid lesions. However, the overlapping appearances of benign and malignant lesions make ultrasound less useful in differentiating solid lesions, resulting in a large number of benign biopsies. Optical tomography using near-infrared diffused light has great potential for imaging functional parameters of 1) tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(157 citation statements)
references
References 19 publications
8
144
1
4
Order By: Relevance
“…For ultrasound imaging guidance, approximations are required for coregistering the two-dimensional (2D) ultrasound images to the 3D optical measurements. 36 Our proposed CT guided DOT imaging system will not have these limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ultrasound imaging guidance, approximations are required for coregistering the two-dimensional (2D) ultrasound images to the 3D optical measurements. 36 Our proposed CT guided DOT imaging system will not have these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…25 33, 35 Zhu and colleagues used ultrasound imaging to guide the DOT imaging. 18,36 These studies have shown substantial improvements in quality and accuracy of DOT imaging with structural priors.…”
Section: Introductionmentioning
confidence: 99%
“…To date, NIR techniques have been combined with several high spatial resolution, structure-specific imaging modalities including X-ray tomosynthesis 57 , ultrasound 66,74 , and MRI [75][76][77] , to study human tissues and small animals. Past experiences have contributed to a variety of imaging systems, imaging geometries, and numerical reconstruction techniques, but…”
Section: Multimodality Techniquesmentioning
confidence: 99%
“…� Two multi-modality based imaging devices (Devices #10a, #10b, #11, Table 3.1) were developed at the University of Connecticut that combined FDPM-based optical imaging and ultrasound into a single hand-held device [66][67][68][69][70][71]. The optical part of each system used 12 pairs of dual wavelength laser diodes (780 nm and 830 nm) and 8 photomultiplier tube (PMT) detectors.…”
Section: Frequency-domain Photon Migration (Fdpm) Based Devicesmentioning
confidence: 99%
“…One group from the University of Connecticut developed hand-held NIR devices with multiple source-detector configurations combined with an ultrasound array [62][63][64][65][66][67][68][69][70][71] as shown in Figure 3.2 (Devices #10a, #10b and #11). The use of multiple sources and detectors enabled area imaging using the NIR component, and a priori information from the ultrasound component enabled 3D tomography, thus determining the target location.…”
Section: Tomographic Imaging-based Devicesmentioning
confidence: 99%